Does income diversification reduce banks’ risk-taking? The difference between large and small banking groups: Evidence from an emerging country - Tran, Thanh Nga Thi (International Journal of Innovative Research and Scientific Studies, 2025)
This paper aims to examine whether income diversification enhances the bank’s risk-taking in emerging markets. It analyzes how this relationship varies between different bank sizes. This study utilizes the S-GMM (system Generalized Method of Moments) estimation [1] to conduct panel data regression. Additionally, it follows the framework outlined by Laeven [2] and Wang et al. [3] to categorize banks into large and small based on their average total assets. Large banks are characterized as institutions with total assets exceeding the median value of assets within the banking sector. In contrast, small banks are identified as those with total assets that fall below this median threshold. The empirical results reveal that income diversification negatively affects banks’ risk-taking in small banks. Conversely, for large banks, the study shows that income diversification has a positive impact on banks’ risk-taking. This study marks the inaugural effort to explore the varying impacts of income diversification on risk-taking behavior among different banking groups in emerging markets. The results may offer valuable insights for researchers, policymakers, and bank managers, enabling them to develop targeted diversification strategies for each banking group to enhance the overall safety of the banking sector in today’s competitive environment.